2010
DOI: 10.1007/s11431-010-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

Advances in estimation methods of vegetation water content based on optical remote sensing techniques

Abstract: Quantitative estimation of vegetation water content (VWC) using optical remote sensing techniques is helpful in forest fire assessment, agricultural drought monitoring and crop yield estimation. This paper reviews the research advances of VWC retrieval using spectral reflectance, spectral water index and radiative transfer model (RTM) methods. It also evaluates the reliability of VWC estimation using spectral water index from the observation data and the RTM. Focusing on two main definitions of VWC-the fuel mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 47 publications
(50 reference statements)
0
38
0
1
Order By: Relevance
“…The sensitivity of the short wave infrared (SWIR) region to changes in vegetation moisture has been widely documented (Ceccato et al, 2001;Gao, 1996;Zhang et al, 2010) and has been implemented in the form of a number of spectral indices. The most well known moisture related vegetation indices are computed as normalized differences between the near-infrared (NIR) reflectance and the SWIR and are commonly referred to in literature as Normalized Difference Water Index (NDWI).…”
Section: Spaceborne Datamentioning
confidence: 99%
“…The sensitivity of the short wave infrared (SWIR) region to changes in vegetation moisture has been widely documented (Ceccato et al, 2001;Gao, 1996;Zhang et al, 2010) and has been implemented in the form of a number of spectral indices. The most well known moisture related vegetation indices are computed as normalized differences between the near-infrared (NIR) reflectance and the SWIR and are commonly referred to in literature as Normalized Difference Water Index (NDWI).…”
Section: Spaceborne Datamentioning
confidence: 99%
“…To estimate leaf EWT, stepwise regression and leaf reflectance model inversion can also be used ( Jacquemoud et al 2000). Many indexes have been introduced and most of them are empirical (Ceccato et al 2002), mostly in the form of the ratio of two reflectance values or a combination of two or more reflectance values (Zhang et al 2010). Zhang et al (2010) have reported five absorption bands for water in 400-2,500 nm spectral region: 970; 1,200; 1,450; 1,930 and 2,500 nm.…”
Section: Research Articlementioning
confidence: 99%
“…Many indexes have been introduced and most of them are empirical (Ceccato et al 2002), mostly in the form of the ratio of two reflectance values or a combination of two or more reflectance values (Zhang et al 2010). Zhang et al (2010) have reported five absorption bands for water in 400-2,500 nm spectral region: 970; 1,200; 1,450; 1,930 and 2,500 nm. Riaño et al (2005b) specified that 1,400-2,500 nm range provides the highest correlation with EWT.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Wang and Qu (2009) comprehensively reviewed progress in soil moisture monitoring using optical, thermal, passive microwave, and active microwave remote sensing techniques. Zhang et al (2010) also reviewed advances in research of vegetation water content retrieval using optical remote sensing, including various vegetation moisture indices and the radiative transfer model (RTM) methods.…”
Section: Introductionmentioning
confidence: 99%